Advanced Prodrug Strategies in Nucleoside and Non-Nucleoside Antiviral Agents: A Review of the Recent Five Years - Smerat, TA; Sinokrot, H; Najjar, A; Karaman, R (Molecules, 2017)
Abstract Background: Poor pharmacokinetic profiles and resistance are the main two drawbacks from which currently used antiviral agents suffer, thus make them excellent targets for research, especially in the presence of viral pandemics such as HIV and hepatitis C. Methods: The strategies employed in the studies covered in this review were sorted by the type of drug synthesized into ester prodrugs, targeted delivery prodrugs, macromolecular prodrugs, other nucleoside conjugates, and non-nucleoside drugs. Results: Utilizing the ester prodrug approach a novel isopropyl ester prodrug was found to be potent HIV integrase inhibitor. Further, employing the targeted delivery prodrug zanamivir and valine ester prodrug was made and shown a sole delivery of zanamivir. Additionally, VivaGel, a dendrimer macromolecular prodrug, was found to be very efficient and is now undergoing clinical trials. Conclusions: Of all the strategies employed (ester, targeted delivery, macromolecular, protides and nucleoside analogues, and non-nucleoside analogues prodrugs), the most promising are nucleoside analogues and macromolecular prodrugs. The macromolecular prodrug VivaGel works by two mechanisms: envelope mediated and receptor mediated disruption. Nucleotide analogues have witnessed productive era in the recent past few years. The era of non-interferon based treatment of hepatitis (through direct inhibitors of NS5A) has dawned.
Review article
Keywords: antiviral; macromolecules; non-nucleoside; nucleoside; prodrug; protide; targeted delivery.